Crucial Dimensions of Human Altruism. Affective vs. Conceptual Factors Leading to Helping or Reinforcing Others - Szuster, Anna (Frontiers in Psychology, 2016)
The aim of the article is to identify factors leading to favorable attitudes towards other people from different social categories. The parts of article reflect divers levels of altruism regulation: from the primary affective responses to environment, through social norms, to abstract moral concept related to good and evil. The latter allow to understand perspective of other people (including those belonging to out-groups), to accept their values, to engage not only into helping behavior but also to support others development.